Characterization and performance evaluations of sodium zeolite-Y filled chitosan polymeric membrane : effect of sodium zeolite-Y concentration - Ahmad, A. L.; Mohd Nawawi, M. G.; So, L. K. (John Wiley & Sons Inc., 2006)
Sodium zeolite-Y (NaY zeolite) filled chitosan polymeric membranes were developed and characterized. The impact of adding different concentrations of NaY zeolite into the homogeneous chitosan membrane was investigated. The surface morphology, mechanical-physical properties, sorption, and pervaporation performance for the dehydration of isopropanol-water mixture separation by the pervaporation process were studied and evaluated. A homogeneous chitosan membrane showed preferential water sorption and permeation compared to isopropanol. The optimum concentration of NaY zeolite added to the homogeneous chitosan membrane was 0.4 wt %, which showed that the dispersion of the NaY zeolite was the most homogeneous and finely covered by the chitosan polymer in the zeolite-chitosan polymer interface. The tensile strength and percent strain at maximum of this membrane were 59.347 MPa and 27.5%, respectively. The sorption experiments showed that the degree of swelling was 6.54% with 1.01 wt % isopropanol sorbed in these membranes. The pervaporation separation tests demonstrated that the NaY zeolite filled chitosan membrane was capable for isopropanol-water mixture separation and improved the pervaporation separation index from 272 (homogeneous chitosan membrane) to 2687.